Setting the stage: performing politics in Theatres of Memory. Issue 3 (3rd July 2019) - Scott-Brown, Sophie
ABSTRACT: The British historian Raphael Samuel is best known as a founding figure in the first British New Left and the driving force behind the history workshop movement which set out to democratise history-making in post Britain. Whilst the workshop has attracted attention for its radical pedagogical practice, Samuel's distinctive approach to the writing of history has been less acknowledged. This paper contends that Theatres of Memory (1994), Samuel's only sole-authored book published in his lifetime, both articulates and performs its author's activist, participatory politics. Written in response to the post-war fragmentation of the political left, Samuel sought a means of escaping the ideological and epistemological impasse that had arisen between factions. Rather than taking a stance on 'people's history', Theatres recognised, and advocated for history making as a common social activity. By making participation its core principle, it reconstituted socialism as an ethics of practice, an adjective rather than a noun, that could accommodate many variations. This article examines how the book enacted this participatory politics through a range of compositional techniques aimed at stimulating active readership. In doing so, it demonstrated, rather than described, a blueprint for the historian's role in an expanding, pluralist, historical culture.